2020
DOI: 10.3390/biology9120463
|View full text |Cite
|
Sign up to set email alerts
|

Lymphatic Vessels and Their Surroundings: How Local Physical Factors Affect Lymph Flow

Abstract: Lymphatic vessels drain and propel lymph by exploiting external forces that surrounding tissues exert upon vessel walls (extrinsic mechanism) and by using active, rhythmic contractions of lymphatic muscle cells embedded in the vessel wall of collecting lymphatics (intrinsic mechanism). The latter mechanism is the major source of the hydraulic pressure gradient where scant extrinsic forces are generated in the microenvironment surrounding lymphatic vessels. It is mainly involved in generating pressure gradients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 98 publications
0
38
0
Order By: Relevance
“…Lymph flow dynamics and the surrounding microenvironment can deeply affect lymphatic spontaneous contractions. Changes in transmural and/or intraluminal pressures, lymph flow-induced wall shear stress, nitric oxide (NO), histamine, fluid osmolarity, local tissue temperature and neuronal modulation by the autonomous nervous system can significantly alter contraction frequency (i.e., chronotropic effect) and/or contraction amplitude (i.e., inotropic effect), continuously modulating and adapting lymph drainage and transport to current needs [21][22][23][24][25][26][27][28][29][30][31][32]. Impaired intrinsic contractility, as well as lymphatic vessels obstruction, may lead to oedema development as a result of tissue fluid imbalance [1].…”
Section: General Overview Of the Lymphatic Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Lymph flow dynamics and the surrounding microenvironment can deeply affect lymphatic spontaneous contractions. Changes in transmural and/or intraluminal pressures, lymph flow-induced wall shear stress, nitric oxide (NO), histamine, fluid osmolarity, local tissue temperature and neuronal modulation by the autonomous nervous system can significantly alter contraction frequency (i.e., chronotropic effect) and/or contraction amplitude (i.e., inotropic effect), continuously modulating and adapting lymph drainage and transport to current needs [21][22][23][24][25][26][27][28][29][30][31][32]. Impaired intrinsic contractility, as well as lymphatic vessels obstruction, may lead to oedema development as a result of tissue fluid imbalance [1].…”
Section: General Overview Of the Lymphatic Systemmentioning
confidence: 99%
“…The extrinsic mechanism, on the other hand, is related to mechanical stresses arising in surrounding tissues then transmitted to the lymphatic vessels by means of fibrous elements of the extracellular matrix [6]. It typically involves vessels located in areas of the body which experience cyclical movements such as the heart or skeletal muscle, lymphatics undergoing cardiogenic activity or respiratory movements, intestinal motility, external compression and arteriolar vasomotion [23,[33][34][35][36][37][38]. These mechanisms rhythmically exert external forces compressing and expanding lymphatic vessels, thus dramatically affecting primary and intraluminal valves dynamics and both ∆P TM and ∆P Lymph .…”
Section: General Overview Of the Lymphatic Systemmentioning
confidence: 99%
“…Lymphatics are important because unlike blood flow, which relies on the heart as a central pump, lymph flow is propelled by forces in the surrounding tissues and by active rhythmic contractions intrinsic to the lymphatic vessels themselves. These intrinsic mechanisms constitute a major force in lymphatic flow and are exquisitely sensitive to the microenvironment, for example, hydraulic pressure, shear stress, local tissue temperature, and sodium [15]. A recent study provides evidence that lymphangiogenesis accompanying arthritis in TNF-transgenic mice reflects intrinsic dysfunction in popliteal lymphatic vessels that is linked to NOSdependent as well as independent impairment in lymphatic vessel dynamics that may drive arthritic damage of the joint [16].…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the patient population of renal allografts showed that higher LVs area density was negatively correlated with allograft functions, not the number density of lymphatic vessels. Worth to mention that, both the lymphatic area and number reflected the density of LVs, but the higher density of lymphatic vessels does not necessarily mean higher lymphatic flow ( 53 , 54 ). The increase in lymphatic area is due to the different diameters of LVs.…”
Section: Discussionmentioning
confidence: 99%